Downscaled Climate Projections Suitable for Resource Management. (10th September 2013) - Thrasher, Bridget; Xiong, Jun; Wang, Weile; Melton, Forrest; Michaelis, Andrew; Nemani, Ramakrishna
Abstract : The general circulation model (GCM) experiments conducted under the Coupled Model Intercomparison Project Phase 5 (CMIP5) [ Taylor et al ., 2012], which is being conducted in preparation for the Intergovernmental Panel on Climate Change's Fifth Assessment Report, provide fundamental data sets for assessing the effects of global climate change. However, efforts to assess regional or local effects of the projected changes in climate are often impeded by the coarse spatial resolution of the GCM outputs, as well as potential local or regional biases in GCM outputs [ Fowler et al ., 2007].